The GOGREEN survey: dependence of galaxy properties on halo mass at z > 1 and implications for environmental quenching. Issue 3 (10th July 2021) - Reeves, Andrew M M; Balogh, Michael L; van der Burg, Remco F J; Finoguenov, Alexis; Kukstas, Egidijus; McCarthy, Ian G; Webb, Kristi; Muzzin, Adam; McGee, Sean; Rudnick, Gregory; Biviano, Andrea; Cerulo, Pierluigi; et al.
ABSTRACT: We use photometric redshifts and statistical background subtraction to measure stellar mass functions in galaxy group-mass (4.5−8 × 10 13 M⊙ ) haloes at 1 < z < 1.5. Groups are selected from COSMOS and SXDF, based on X-ray imaging and sparse spectroscopy. Stellar mass ( M stellar ) functions are computed for quiescent and star-forming galaxies separately, based on their rest-frame UVJ colours. From these we compute the quiescent fraction and quiescent fraction excess (QFE) relative to the field as a function of M stellar . QFE increases with M stellar, similar to more massive clusters at 1 < z < 1.5. This contrasts with the apparent separability of M stellar and environmental factors on galaxy quiescent fractions at z ∼ 0. We then compare our results with higher mass clusters at 1 < z < 1.5 and lower redshifts. We find a strong QFE dependence on halo mass at fixed M stellar ; well fit by a logarithmic slope of d(QFE)/dlog ( M halo ) ∼ 0.24 ± 0.04 for all M stellar and redshift bins. This dependence is in remarkably good qualitative agreement with the hydrodynamic simulation bahamas, but contradicts the observed dependence of QFE on M stellar . We interpret the results using two toy models: one where a time delay until rapid (instantaneous) quenching begins upon accretion to the main progenitor ('no pre-processing') and one where it starts upon first becoming a satellite ('pre-processing'). Delay times appear to be halo mass-dependent, with a significantly stronger dependence required without pre-processing. We conclude that our results support models in which environmental quenching begins in low-mass (<10 14 M⊙ ) haloes at z > 1.